PRAKTIK COST PLUS BIL WAKALAH DALAM PEMBIAYAAN SEMBAKO DI BMT UGT SIDOGIRI CABANG AROSBAYADASAR-DASAR - A Taufiq Bahari (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2020)
The practice of Cost Plus bil Wakalah in the financing of basic necessities at BMT UGT Sidogiri, Arosbaya Branch includes: (1) to become a Cost Plus customer, if you have to go to BMT UGT sidogiri by disclosing what your needs are, (2) providing an explanation of the Cost Plus bil Wakalah before the contract is correct -You really understand, (3) in the procurement of goods by the customer himself because the customer is the representative for buying goods, (4) the mechanism of ownership of the goods, namely if the customer has submitted the purchase result as evidence, the BMT sells the goods to the customer, and the goods it officially becomes the property of the customer (5) guarantee for Cost Plus bill wakalah financing in the form of gold or motorized vehicle certificates, (6) the profit from Cost Plus bill Wakalah; for customers, they can buy the goods they want, for BMT; get a margin from Cost Plus, (7) if there is a delay in installments then you have to give alms to DANSOS, if there is udur syar'i it is understandable by the BMT, (8) you don't have to pay on time if the customer really doesn't have it to pay.